Efektivitas Modul Larutan Elektrolit dan Nonelektrolit berorientasi Chemistry Triangle terhadap Hasil Belajar Peserta Didik - Hardeli Hardeli; Annisa Citra (Universitas Negeri Padang, 2021)
Electrolyte and nonelectrolyte solution module oriented to chemistry triangle have been experimented using a randomized pretest-posttest control group design. This study goals to reveal the level of effectiveness of electrolyte and nonelectrolyte solution module oriented to chemistry triangle on learning outcomes of class X MIA at SMAN 15 Padang. Research instruments is multiple choice tests that have been valid, reliable, differentiating power, and indexing difficulties that could measure student learning outcomes. The level of effectiveness of electrolyte and nonelectrolyte solution module oriented to chemistry triangle is known through the N-gain test. N-gain test results with a value of g=0.46 states that electrolyte and nonelectrolyte solution module oriented to chemistry triangle is effective in improving student learning outcomes on medium criteria.